Dicer-2-dependent activation of Culex Vago occurs via the TRAF-Rel2 signaling pathway. - Prasad N Paradkar; Jean-Bernard Duchemin; Rhonda Voysey; Peter J Walker (Public Library of Science (PLoS), 2014)
Despite their importance as vectors of human and livestock diseases, relatively little is known about innate antiviral immune pathways in mosquitoes and other insects. Previous work has shown that Culex Vago (CxVago), which is induced and secreted from West Nile virus (WNV)-infected mosquito cells, acts as a functional homolog of interferon, by activating Jak-STAT pathway and limiting virus replication in neighbouring cells. Here we describe the Dicer-2-dependent pathway leading to WNV-induced CxVago activation. Using a luciferase reporter assay, we show that a NF-κB-like binding site in CxVago promoter region is conserved in mosquito species and is responsible for induction of CxVago expression following WNV infection. Using dsRNA-based gene knockdown, we show that the NF-κB ortholog, Rel2, plays significant role in the signaling pathway that activates CxVago in mosquito cells in vitro and in vivo. Using similar approaches, we also show that TRAF, but not TRAF-3, is involved in activation of Rel2 after viral infection. Overall the study shows that a conserved signaling pathway, which is similar to mammalian interferon activation pathway, is responsible for the induction and antiviral activity of CxVago.